2017
DOI: 10.1016/j.jmb.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The Von Willebrand Factor A1–Collagen III Interaction Is Independent of Conformation and Type 2 Von Willebrand Disease Phenotype

Abstract: The blood von Willebrand factor (VWF) mediates platelet adhesion to injured vessels by sequestering platelets from blood flow and depositing them to collagen and other exposed subendothelial matrix proteins. This process of capturing platelets to facilitate formation of platelet plugs occurs through transient interactions with platelet glycoprotein Ibα via the VWF A1 domain which also binds collagen. Using a conformationally diverse collection of natively folded and mutation-induced misfolded von Willebrand Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Mutations affect secondary structures both local to and Cterminally distant from the mutation site within the globular A1 domain indicating a potential for allostery. The structural dynamic properties of the wild-type A1 are conserved in each of the recombinant expression constructs and, within experimental error, are identical to the A1 dynamics in plasma VWF, indicating that the single A1 domain and A1A2A3 tridomain constructs used here, and in our prior publications [10][11][12]20,21,27,[29][30][31][32][34][35][36][37], are accurate models for structural and functional studies of VWD. Overall, the results indicate that the intrinsic conformational dynamics observed in recombinant domain fragments of VWF are preserved in the biologically-relevant multimeric forms of VWF present in blood plasma.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Mutations affect secondary structures both local to and Cterminally distant from the mutation site within the globular A1 domain indicating a potential for allostery. The structural dynamic properties of the wild-type A1 are conserved in each of the recombinant expression constructs and, within experimental error, are identical to the A1 dynamics in plasma VWF, indicating that the single A1 domain and A1A2A3 tridomain constructs used here, and in our prior publications [10][11][12]20,21,27,[29][30][31][32][34][35][36][37], are accurate models for structural and functional studies of VWD. Overall, the results indicate that the intrinsic conformational dynamics observed in recombinant domain fragments of VWF are preserved in the biologically-relevant multimeric forms of VWF present in blood plasma.…”
supporting
confidence: 52%
“…Prior structure function studies in our lab have demonstrated that mutations causing type 2B and type 2M von Willebrand disease can alter the proper folding of the A1 domain. Of the nineteen type 2 VWD variants characterized, twelve have been identified that misfold the A1 domain, six in each phenotype [10,34]. Here, we show that the far-UV CD spectroscopy used to characterize single A1 domain becomes less sensitive to conformational changes in the larger A1A2A3 recombinant fragments of VWF, thereby eliminating its utility in providing proof that VWD mutations misfold A1 in multimeric VWF.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These two types of domains have been shown to be involved in collagen binding [ 23 ]. A single Cna protein B-type domain, identical to those found in this study, is encoded by cnaA [ 11 ] and the vWF type A domain is also involved in collagen binding [ 24 ]. Thus, it may be suggested that these adhesion properties play an important role when C. perfringens strains attach to collagen in the intestine of turkeys and cause NE.…”
Section: Main Textmentioning
confidence: 86%
“…Finally, mutations in A2 cause defective intracellular transport or enhance proteolysis of a scissile bond recognized by the soluble blood metalloprotease (ADAMTS13), which helps regulate the multimeric size of vWF (Keeney and Cumming, 2001 ). Some vWD mutations that change A1-GP1bα binding specificity result in local misfolding of the A1 domain (Tischer et al, 2014 , 2017 ; Zimmermann et al, 2015 ; Machha et al, 2017 ) causing both gain and loss of function phenotypes. Two such mutations are V1314D, a gain of function mutation that causes increased platelet adhesion, and F1369I, a loss of function mutation that does not adhere to platelets at all.…”
Section: Comparison Of Kinetically Controlled Denaturation Isotherms mentioning
confidence: 99%